2021
DOI: 10.1007/s00259-021-05597-5
|View full text |Cite
|
Sign up to set email alerts
|

A metabolically stable PET tracer for imaging synaptic vesicle protein 2A: synthesis and preclinical characterization of [18F]SDM-16

Abstract: Purpose To quantify the synaptic vesicle glycoprotein 2A (SV2A) changes in the whole central nervous system (CNS) under pathophysiological conditions, a high affinity SV2A PET radiotracer with improved in vivo stability is desirable to minimize the potential confounding effect of radiometabolites. The aim of this study was to develop such a PET tracer based on the molecular scaffold of UCB-A, and evaluate its pharmacokinetics, in vivo stability, specific binding, and nonspecific binding signals i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Several [ 18 F]-labeled candidates have now been evaluated ( Patel et al, 2020 ), especially UCB-J derivatives including [ 18 F]MNI-1126 ( Constantinescu et al, 2019 ), also named [ 18 F]-SDM-8 and described by Li et al (2019a) and then referred as [ 18 F]-SynVesT-1 ( Li et al, 2021 ; Naganawa et al, 2021b ). Other recently developed compounds are [ 18 F]-SynVesT-2 ( Cai et al, 2020 ) and [ 18 F]-SDM-16 ( Zheng et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 99%
“…Several [ 18 F]-labeled candidates have now been evaluated ( Patel et al, 2020 ), especially UCB-J derivatives including [ 18 F]MNI-1126 ( Constantinescu et al, 2019 ), also named [ 18 F]-SDM-8 and described by Li et al (2019a) and then referred as [ 18 F]-SynVesT-1 ( Li et al, 2021 ; Naganawa et al, 2021b ). Other recently developed compounds are [ 18 F]-SynVesT-2 ( Cai et al, 2020 ) and [ 18 F]-SDM-16 ( Zheng et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 99%
“…Our results showed that acrolein significantly reduced the number of dendritic spines of cortical neurons after 4 weeks of administration, and the dendritic spines were swollen and dysplasia (Figure 2a ). Synapsin 1 and postsynaptic density 95 (PSD95) reflect the related functions of pre‐ and post‐synapses, respectively (Zhang, Wu, et al, 2021 ), while Synaptic Vesicle Glycoprotein 2A (SV2A) is a key protein that reflects the function of synaptic transmission (Zheng et al, 2021 ). The expression of these synapse‐related proteins in the hippocampus (PSD95: p < 0.05; SV2a and Synapsin1: p < 0.01) and cortex (SV2A: p < 0.05; PSD95 and Synapsin1: p < 0.01) of mice was significantly down‐regulated after administration of acrolein for 4 weeks (Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…There are several 18 F-labeled SV2A tracers, i.e., [ 18 F]UCB-H ( Warnock et al, 2014 ), [ 18 F]UCB-J ( Li et al, 2019b ), [ 18 F]SynVesT-1 ( Li et al, 2019a , 2021 ), [ 18 F]SynVesT-2 ( Cai et al, 2020b ), and [ 18 F]SDM-16 ( Zheng et al, 2021 ), with different specific binding, brain kinetics, and peripheral metabolic rates. Figures 1A,B show the tracer kinetics in rhesus macaques and rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not likely to influence the quantitative analysis using this tracer, as [ 18 F]SynVesT-2 has rapid brain kinetics and only requires ∼30 min scanning time for reliable quantitative analysis based on our previous non-human primates’ results ( Cai et al, 2020b ). [ 18 F]SDM-16, a derivative of UCB-A ( Estrada et al, 2016 ) is the most metabolically stable SV2A PET tracer so far ( Zheng et al, 2021 ). Our evaluations of [ 18 F]SDM-16 in rodents are ongoing and the results will be reported in due course.…”
Section: Introductionmentioning
confidence: 99%